1984
DOI: 10.1177/002221948401700907
|View full text |Cite
|
Sign up to set email alerts
|

Family Interaction and Learning Disabilities

Abstract: This study explored the relationship of family systems theory to understanding the problems associated with learning disabilities in school children. Hypotheses were developed relating family interaction to classification of children as learning disabled (LD), emotionally disturbed (ED) and normal (N). The parents of 90 children (n = 30 LD, 30 ED, 30 N) completed The Family Adaptability and Cohesion EvaluationScales (FACES). Results provided partial support for the hypotheses, and were discussed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Families with children who have learning difficulties have been found to be more chaotic and less stable than families whose children do not exhibit these difficulties (Amerikaner & Omizo, 1984). Because chaotic and unstable families are at risk for less than optimal parenting early intervention and prevention strategies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families with children who have learning difficulties have been found to be more chaotic and less stable than families whose children do not exhibit these difficulties (Amerikaner & Omizo, 1984). Because chaotic and unstable families are at risk for less than optimal parenting early intervention and prevention strategies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Communication was found to be unclear, rules were not clearly defined, and marital breakup was common in these families (Amerikaner & Omizo, 1984). Ditton, Green, and Singer (1987) found that families with a child who has learning difficulties exhibit more communication deviances such as commitment or referent problems which leave listeners confused concerning intended meaning.…”
Section: Parenting Children With Learning Difficultiesmentioning
confidence: 99%
“…The analysis revealed that 87 percent of parents of children with LD were rated high in communication deviance; 77 percent of nonlabeled children's parents were rated low in communication deviance. Similarly, Owen, Adams, Forest, Stolz, and Fisher (1971) and Amerikaner and Omizo (1984) found that families of children with LD scored in the chaotic (versus functional) range on family adaptability, were generally less cohesive and more disorganized and disengaged than families of nondisabled and exceptionally abled children.…”
Section: Exceptional Children and Parental Communication Stylesmentioning
confidence: 91%
“…Although professionals have long recognized the need to establish a positive relationship between the school, the home, and the community and the role these environments play in the emotional, cognitive, and social development of children (Hurwitz & Polvistok, 1985;Peters & Stephenson, 1978;Sanborn, 1979;Zigler, 1972), the importance of this relationship for the understanding and the educating of mildly handicapped students is just emerging (Amerikaner & Omizo, 1984 population focus only on one environment-either the school or the home or the community-without incorporating the important link between this important triad.…”
Section: The Need For Cooperative Relationshipsmentioning
confidence: 99%